Influence of pre-induced mental fatigue on tactical behaviour and performance among young elite football players - Correia da Silva, D.; Afonso, J.; Augusto, D.; Petiot, G. H.; Martins Filho, C. C.; Vasconcellos, F. (International Journal of Sport and Exercise Psychology, 2023)
Elite athletes are reportedly more resistant to mental fatigue and are less negatively influenced by pre-induced mental fatigue. However, such evidence has not been verified in the context of open sports, such as football. This study investigated the effects of pre-induced mental fatigue on tactical behaviour and performance among Brazilian male elite football players under 17 years (n = 18). The System of Tactical Assessment in Soccer (FUT-SAT) was utilised to assess the players` tactical behaviour and performance. A [stratified] sample of players was assessed, with and without pre-induced mental fatigue. The Stroop test was used to induce mental fatigue. The Shapiro-Wilk test was used to verify the distribution of the data, and the paired t and Wilcoxon statistical tests were conducted to compare the paired groups of players. The results showed that players decreased the number of actions in the offensive and defensive phases under the condition of pre-induced mental fatigue. Contrarily, these players increased the efficiency of their actions and consequently improved their tactical performance. This probably occurred because players were more selective in their actions and focused more on the most relevant actions to solve problems when in play. It was concluded that young players could adapt their tactical actions, whether offensive or defensive, under the conditions of pre-induced mental fatigue.